Adversarial justice in the face of new trends in alternative resolution of mass consumer damages. Adjustment to the Spanish model - Moreno Cordero, Gisela (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Relatively recently, Directive (EU) 2020/828 of the European Parliament and of the Council of 25 November on representative actions for the protection of consumers’ collective interests was adopted. Its main objective has been to ensure that consumers have at least one procedural mechanism capable of effectively protecting their collective interests. However, the Directive is based on an adversarial model of proven ineffectiveness that did not take into account the new dispute resolution models adopted by some Member States, whose effectiveness is indisputable in terms of time and results. By means of these new models (new technologies) it is possible to quickly and easily obtain redress for the massive damage caused to consumers through voluntary agreements, without the need to resort to a procedure. Taking as a starting point the extensive comparative experience and scientific doctrine, our proposal is aimed at evaluating the possible introduction of new technologies -regulatory redress and the Ombudsman- in the Spanish legal system in those consumer sectors where this is feasible.
Keywords: Collective actions; regulatory redress; consumer ombudsman